Implementasi Mode Deep Sleep pada Sistem Pendeteksi Asap Rokok Berbasis LoRa di Pesantren - Fathurahman, Mohamad (Spektral, 2024)
Smoking behavior is found in pesantren (boarding schools) as well as in non-boarding school zones. Although there is a no-smoking rule in pesantren, there are still many students who smoke in secret where one of the most common places for them to smoke is inside the dormitory toilets and dormitories. Most often used as a place to smoke is inside the dormitory toilet and this behavior is an offense. This behavior is a violation. The purpose of this research is to design a cigarette smoke detector that can help teachers or supervisors in supervising students. students who are secretly smoking in the bathroom. who are smoking in the restroom. The device uses a CO sensor and a CO2 sensor as sensors to detect the presence of cigarette smoke. In an effort to of cigarette smoke, a smoker alarm system is created that can warn the can provide a warning to the pesantren supervisor if there is an indication of the presence of cigarette smoke in a toilet cubicle. Presence of cigarette smoke in a toilet cubicle. A LoRa module is used for data transmission. LoRa module is used. For the data that is sent from the next sensor is sent to the firestore database using the MQTT protocol and Node-RED as programming. using Node-RED as programming. This system can send This system can send data up to a radius of 180 meters under NLOS conditions. When testing the CO and CO2 sensor testing, there were differences in gas concentration values when the sensor was not influenced by smoke and when the smoke was influenced by the sensor. sensor was affected by smoke. Node Transmitter nodes using the Deep Sleep feature receive an additional 79.8% uptime.